El culte de l'arcàngel Sant Miquel a la Seu Episcopal de Vic (segles X-XI) - Ordeig i Mata, Ramon (Miscel·lània litúrgica catalana, 2019)
The church of Sant Miquel Arcàngel (Saint Michael the Archangel) in Vic was endowed by Count Sunyer in the year 948, on the occasion ofthe consecration carried out by Bishop Guadamir. It was of a funerary character, dedicated as it was to the archangel who weighs souls and leads them to heaven the same archangel who had appeared in the year 492 in a cave on Mount Gargano, subsequently a celebrated place of pilgrimage. The story of the apparition is recorded in the martyrologies copied in the 10th and 11th centuries in the Vic Cathedral. A donation of the year 1009 pro edificio of the church of Saint Michael shows that works were carried out there. This allows it to be suggested that a colonnade was erected in the church, as a symbol of the forest of Gargano, which Bishop Oliba would presumably have reused for the Romanesque crypt. This structure substituted the crypt of Saint Michael, representing the Archangel's grotto, where Bishop Borrell was buried in 1018.